THE IMPLEMENTATION OF VIRTUAL LABORATORY BASED LEARNING USING PHET SIMULATION ON KINETIC THEORY OF GASES TOPIC FOR INCREASING THE LEARNING OUTCOME OF GRADE XI STUDENTS AT KANJENG SEPUH SIDAYU ISLAMIC SENIOR HIGH SCHOOL - FARIDAH WADLIKH, SITI (Inovasi Pendidikan Fisika, 2017)
The research entitled “The Implementation of Virtual Laboratory Based Learning Using PhET Simulation on Kinetic Theory of Gases Topic for Increasing The Learning Outcome of Grade XI Students At Kanjeng Sepuh Sidayu Islamic Senior High School” aimed to analyze students learning outcome after joining virtual laboratory based learning using PhET Simulation on kinetic theory of gases topic at Kanjeng Sepuh Islamic Senior High School. This research used pre-experimental design with one group pre-test post-test design. The participants of this study were students of XI MIA 1 which are chosen using purposive sampling technique as an experiment class. The results of this study on the form of pre-test and post-test data were analyzed using normality test, homogenity test, t test and normalized gain test. The result of this study shows that the research sample comes from normal population. The students learning outcome after joining the learning activity is better than before which was showed by one tailed t test analysis had tcalc of 15,30. For the enhancement of students learning outcome based on n-gain test was 0,64 which are categorized as middle enhancement. The implementation of virtual laboratory based learning using PhET Simulation at Kanjeng Sepuh Islamic Senior High School gained very good mark.   Keywords : virtual laboratory based learning, PhET Simulation, kinetic theory of gases